Hadith #2502 - Sunan Abi Dawud - Abu Umama bin Sahl; al-Qasim bin 'Abdur Rahman القاسم بن عبد الرحمن بن عبد الله; al-Waleed bin Muslim bin Shahab الوليد بن مسلم بن شهاب; Amr bin 'Uthman عمرو بن عثمان بن عفان; Yahya bin al-Harith al-Dhamari يحيى بن الحارث الذماري (Sunan Abi Dawud)
Abu Hurairah reported the Prophet (ﷺ) as saying “He who dies without having fought or having felt fighting (against the infidels) to be his duty will die guilty of a kind of hypocrisy.”
Grade: Sahih